2022
DOI: 10.1177/09596518221103040
|View full text |Cite
|
Sign up to set email alerts
|

Development of autonomous vehicle lateral control using time-varying asymmetric barrier Lyapunov function via ADRC approach

Abstract: In a surface vehicle ride, the passenger’s comfort is desirable, ensuring safety under various tight constraints. To consider this requirement, this article has proposed a lateral control for autonomous vehicle considering the lateral offset error constraints. A reduced-order dynamics of the vehicle has been considered for improving and easy implementation of backstepping. A nonlinear control has been developed by utilizing the Time-varying Asymmetric Barrier Lyapunov Function via the Active Disturbance Reject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…This method fully considered lateral offset error constraints and estimated unknown states and disturbances through ESO. The experimental results showed that this method greatly stabilized the control signal and reduced tracking error (Parkash and Swarup, 2022).…”
Section: Related Workmentioning
confidence: 91%
“…This method fully considered lateral offset error constraints and estimated unknown states and disturbances through ESO. The experimental results showed that this method greatly stabilized the control signal and reduced tracking error (Parkash and Swarup, 2022).…”
Section: Related Workmentioning
confidence: 91%